Improving home haemodialysis : stability evaluation of routine clinical chemistry analytes in blood samples of haemodialysis patients - Nonkes, Lourens J.P (Array, 2018)
Introduction: A growing number of dialysis patients is treated with home haemodialysis. Our current pre-analytical protocols require patients tocentrifuge the blood sample and transfer the plasma into a new tube at home. This procedure is prone to errors and precludes accurate bicarbonatemeasurement, required for determining dialysate bicarbonate concentration and maintaining acid-base status. We therefore evaluated whethercooled overnight storage of gel separated plasma is an acceptable alternative.Materials and methods: Venous blood of 34 haemodialysis patients was collected in 2 lithium heparin blood collection tubes with gel separator(LH PSTTM II, REF 367374; Becton Dickinson, New Jersey, USA). One tube was analysed directly for measurement of bicarbonate, potassium, calcium,phosphate, glucose, urea, lactate, aspartate aminotransferase (AST), and lactate dehydrogenase (LD); whereas the other was centrifuged and storedunopened at 4 °C and analysed 24 h later. To measure analyte stability after 24 h of storage, the mean difference was calculated and compared to thetotal allowable error (TEa) which was used as acceptance limit.Results: Potassium (Z = - 4.28, P <0.001), phosphate (Z = - 3.26, P = 0.001), lactate (Z = - 5.11, P <0.001) and AST (Z = - 2.71, P = 0.007) concentrationswere higher, whereas glucose (Z = 4.00, P <0.001) and LD (Z = 3.13, P = 0.002) showed a reduction. All mean differences were smaller thanthe TEa and thus not clinically relevant. Bicarbonate (Z = 0.69, P = 0.491), calcium (Z = - 0.23, P = 0.815) and urea (Z = 0.81, P =0.415) concentrationswere stable.Conclusions: Our less complex, user-friendly pre-analytical procedure resulted in at least 24 h stability of analytes relevant for monitoring haemodialysis,including bicarbonate. This allows shipment and analysis the next day.